ANALISIS PENGARUH PEMBERDAYAAN DAN KINERJA UMKM TERHADAP KESEJAHTERAAN PELAKU UMKM DI KABUPATEN SIKKA-NTT - Samosir, Magdalena Silawati; Utama, Made Suyana; Marhaeni, A.A.I.N (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.05.TAHUN 2016, 2016)
The purpose of this study was to analyze the effect of empowering MSME onMSME performance, analyze the influence of empowerment and performance of MSMEs in the welfare of SMEs in SikkaRegency-East Nusa Tenggara, and analyze the indirect effect of empowerment onwelfare through the performance of MSME in Sikka Regency- East Nusa Tenggara. Data source of this research was primary data obtained from the direct interviews using questionnaires to 105 MSME and secondary data were obtained from the Office of Cooperative in Sikka Regency - East Nusa Tenggara. Sample collectionused nonpropability sampling method with accidental sampling technique. Data analysis technique of this research was descriptive analysis and PLS. The resultof statistical analysis showed the average of empowerment variables were variables with the highest loading value i.e.0.901, in the performance variable,the highest loading value was capital variables i.e. 0,856 and welfare variable,the highest loading value was the education variable, 0.819. While the resultof PLS analysis concluded that the MSME empowerment had a significant and positive effect on the performance of MSME and empowerment and performance of MSME hada significant and positive effect on the welfare of MSME, and performance significantly had a role to mediate the effect of empowerment on the welfare of MSME in Sikka Regency- East Nusa Tenggara. Therefore there should be an increase in empowerment and performance of MSME in order to increase the degree of welfare of MSME.
Keywords: Empowerment, Performance, Welfare